If it's not what You are looking for type in the equation solver your own equation and let us solve it.
m in (-oo:+oo)
(2/3)*(m-8) = 9 // - 9
(2/3)*(m-8)-9 = 0
2/3*(m-8)-9 = 0
2/3*(m-8)-9 = 0
2/3*m-43/3 = 0
2/3*m-43/3 = 0
2/3*m-43/3 = 0 // + 43/3
2/3*m = 43/3 // : 2/3
m = 43/3/2/3
m = 43/2
m = 43/2
| 35=3x+2(x-5) | | 24000/X=0 | | 0.2x-3.4=0.5x-2.5 | | 6=1-3p | | 130=24x+2 | | 18x-6=120 | | 6=1-3p+2 | | 5x-2=2(5x+1)-1 | | 3(18-2^3)/2 | | P=7/100q-250 | | Y=X^4-6x^2+12 | | 6-7x-2=-17+4x-12 | | 3(2x+7)=3x-30 | | 18y+7=29 | | 19=5y+24 | | (27/9)^2-6 | | 35x+1=36x-1 | | -100/-20 | | 20x-8=18x+6 | | w^4-9w^2+8=0 | | (2x+7)4=124 | | B+2+3=7 | | 20x-2=18x+8 | | -3x+7=1-3x | | 0.7(x+9)=15 | | 20x+5=19x+11 | | -2x+13=.5x-20 | | 26d=520 | | 231+10x=18y+5 | | 6x^2+10=2x^2+30 | | m+-255=2 | | (7y+8)-(5+6y)=6 |